Applications Used in Distance Education for English Language Classrooms - Ipek, Omer Faruk; Ustunbas, Zafer (JET (Journal of English Teaching), 2021)
Integration of technology in the teaching/learning process has caused many changes in education in recent years. In addition, due to the pandemic that surrounded the world at the beginning of 2020, schools had to switch from face-to-face to distance education; therefore, the need for technology use and expansion of online applications became inevitable. As a result of this massive change in education and the emergence of online applications as language learning tools, this evaluation study investigates Edpuzzle, Flipgrid, Padlet, and Quizlet that are created as educational applications used in English language classes. The paper starts with the hegemony of technology in education and then continues with the evaluation of these online applications. Lastly how to use these applications effectively in English as a foreign language (EFL) classrooms is discussed. It can be reported that EDpuzzle can mostly be used for authentic video sessions; Flipgrid is effective on online speaking skills; Padlet is helpful with students’ writing skills, and lastly, Quizlet is beneficial for vocabulary teaching. It can be concluded that online applications are likely to result in effective assistance of learning and practicing both for language teachers/students and learning/teaching processes.